2016
DOI: 10.1073/pnas.1600561113
|View full text |Cite|
|
Sign up to set email alerts
|

Growth hormone is permissive for neoplastic colon growth

Abstract: Fig. 6. GH induces EMT, suppresses apoptosis, and increases motility. Western blot analysis of PTEN and EMT factors in (A) hNCC and (B) HCT116 cells treated with indicated doses of GH for 24 h. (C) Western blot analysis of cleaved caspase 3 in cells treated with GH (500 ng/mL) for 24 h. Experiments were performed at least three times, and representative results shown. (D) Migration of hNCC and HCT116 cells treated with GH (500 ng/mL) and harvested 48 h after plating. (E) Migration of HCT116 cocultured for 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
103
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 98 publications
6
103
0
Order By: Relevance
“…P53 phosphorylation and stabilization results in temporal proliferation block to allow cells to repair DNA damage (69,70). We previously showed that GH suppresses total p53 (24). Here, we show that GH also reduces ATM activity and destabilizes p53, thus enabling some cells to evade p53-dependent senescence or apoptosis (71,72) and to continue proliferating despite accumulation of unrepaired DNA damage.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…P53 phosphorylation and stabilization results in temporal proliferation block to allow cells to repair DNA damage (69,70). We previously showed that GH suppresses total p53 (24). Here, we show that GH also reduces ATM activity and destabilizes p53, thus enabling some cells to evade p53-dependent senescence or apoptosis (71,72) and to continue proliferating despite accumulation of unrepaired DNA damage.…”
Section: Discussionmentioning
confidence: 55%
“…Excess pituitary tumor GH secretion in acromegaly results in soft tissue overgrowth and increased adenoma formation in the colon, skin, thyroid, and prostate (21), and it is associated with increased risk for colorectal carcinoma (22,23). GH triggers epithelial-to-mesenchymal transition, creating a proneoplastic mucosal environment (24)(25)(26)(27). By contrast, abrogated GH signaling is associated with decreased cancer development in humans and in mice (20,(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the recent paper by Chesnokova and colleagues found that using pegvisomant to block colon cell GH receptors in vitro and in patients with acromegaly increased p53 expression, thus suggesting that blocking GH signaling may yield tumor-protective effects. (Chesnokova, et al 2016)…”
Section: Discussionmentioning
confidence: 99%
“…In a preclinical model, local increases in colon GH generated a tumor microenvironment that was permissive for neoplastic colon growth in mice [6]. In addition, in a meta-analysis that included 9 controlled studies of 701 patients with acromegaly and 1573 controls, there was a higher risk of colon cancer in patients with acromegaly (14/304 [4.6%]) than in control patients (8/627 [1.2%]) [2].…”
Section: Discussionmentioning
confidence: 99%